Does the education level of refugees affect natives' attitudes? - Philipp Lergetporer; Marc Piopiunik; Lisa Simon (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
In recent years, Europe has experienced a large influx of refugees. While natives' attitudes toward refugees are decisive for the political feasibility of asylum policies, little is known about how these attitudes are shaped by information about refugees' characteristics. We conducted a survey experiment with a representative sample of more than 4,000 adults in Germany in which we randomly provide information about refugees' education level. Information provision strongly increases respondents' beliefs that refugees are well educated. The information also increases labor market competition concerns, decreases fiscal burden concerns, and positively affects general attitudes toward refugees. We perform several robustness analyses in additional experiments with more than 5,000 university students. In sum, we show that correcting misperceptions about refugees' education level has profound effects on natives' attitudes.
Keywords: F22; J24; D83; C91; 330; Refugees; information provision; education; survey experiment; labor market